The Relationship Between Culture Shock And Self-Esteem Of New Students Outside Java Island At University Of Jember - Ami Allaili; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (KHD-Production, 2021)
The main problem faced by the new students is the pressure on themselves that affects academics and non-academics. This pressure makes new students feeling of uncomfortable caused by new environment which called a culture shock. A person who experiences a culture shock will affect their physical and emotional condition. Someone who has negative feelings about themselves and others can cause individuals to experience low self-esteem. This study aims to analyze the relationship between culture shock and the self-esteem of new students outside Java at the University of Jember. The researcher used quantitative cross-sectional analytical research design, using purposive sampling technique to get a sample of 106 students, and using culture culture shock and the Self Esteem Inventory (SEI) questionnaire. The results of the study using the tau_b kendall statistical test obtained the value p = 0.330 and r = -0.093 so that p> α. So, there is no surprising cultural connection with the self-esteem of new students outside Java at the University of Jember. Suggestions from this study are expected that educational institutions can provide training, development and psychological assistance as long as students undergo an adaptation process in a new environment